Motivasi Petani dalam Pemanfaatan Lahan Pesisir untuk Perkebunan Kelapa di Kecamatan Karimunjawa, Kabupaten Jepara - Muhammad Pambudi Utomo; Retno Setyowati; Suminah Suminah (Universitas Sebelas Maret, 2022)
This study aims to examine the factors forming the motivation of farmers in the use of coastal land for coconut plantations, to examine the level of motivation of farmers in the use of coastal land for coconut plantations, to examine the relationship between motivational forming factors and the level of motivation of farmers in the use of coastal land for coconut plantations. The research location is in Karimunjawa Sub-district with the consideration that sub-district is one of the sub-districts in the Jepara Regency which has the largest coconut plantation area and the largest yields. The sampling technique used is the Census Data analysis using Spearman rank. The results showed that the motivation-forming factors were age 37 to 43 years, elementary formal education, nonformal education (X1) in the rare category, a land area (X2) less than 0.5 ha, the majority of farmers' income (X3) is less than 2.000.000 IDR, cosmopolitan (X4) 1 to 2 times, the role of extension workers (X5) in the category of quite a role, family support (X6) in the supporting category, the role of community leaders (X7) in the role category and price assurance (X8) in the easy category. The level of motivation of farmers in the use of coastal land for coconut plantations (Y) includes existence motivation (Y1) in the want category, relatedness motivation (Y2) in the unwilling category and growth motivation (Y3) in the less wanted category. There is no significant relationship between X1, X2, X4, X5, X6, X7 and X8 on the Y variable, while only X3 has a significant relationship to the Y variable.